DIGITAL FOOTPRINTS IN THE ERA OF NEW MEDIA - Nikolić, Jovana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
New media is essential part of everyday practices of individuals. Research shows that 80% respondents on the territory of Serbia checks their social media accounts several times a day. For average consumer this means that they are in constant contact with friends and that they have easy access to information and news. For companies continuous presence is a source of significant data about habits and opinions of consumers. Question remains: How can users create their own digital footprints in various ways? How big companies can abuse data? If data became oil of 21st century, does that mean users have become commodities? The aim of this paper is to show what is happening with users’ privacy when engaging with new media, through mapping characteristics of new media, current centers of power in digital world, defining the concepts of digital footprints and privacy in online sphere and through case study of privacy violations.
Keywords: new media; digital footprints; social media; applications; data; Facebook